Academic IS Risk Management using OCTAVE Allegro in Educational Institution - Vincentius Gerardo; Ahmad Nurul Fajar (Universitas Bina Darma, 2022)
Today, the use of technology is a common thing that is used to support everyday life. However, this technology also carries risks that can compromise the security of information in organizations. Kalbis Institute is a private campus in the East Jakarta area that has been established since 2012. The academic information system used there includes all actors in the campus environment. This risk analysis is carried out to see and understand what risks exist in the current information system. This risk analysis will assess how likely there are threats and vulnerabilities to information systems. This study uses the OCTAVE Allegro method with the help of the OCTAVE Allegro Worksheet. The purpose of this study is to conduct a risk analysis of the academic information system at Kalbis Institute. The result of this study is to look at risk assessments and recommendations for strategies to protect information systems within organization.